Preparation of Hydrous Ruthenium Oxide/Activated Carbon Electrode and Its Supercapacitive Performance in 6 M KOH - Mohd Abid, M. A. A.; Seman, R.N.A.R.; Effendi, S.M. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Hydrous ruthenium oxide (RuO2) and activated carbon (AC) denoted as RuO2/AC composite electrodes were prepared by combining sol–gel and conventional slurry processing techniques. In this paper, several different compositions of composite electrode slurries were fabricated using RuO2 and AC powders. Benefits from the combined advantages of both RuO2 and AC in such a unique structure were the RuO2/AC composite electrode supercapacitors exhibited the specific capacitance (5.10 F g-1 for RuO2 50 wt%) and also have good cycling stability. These findings demonstrated the importance and great potential of RuO2/AC composites in the development of the energy-storage system especially for the high power supercapacitor electrode.